PROBLEMS OF DEVELOPING THE SEMANTIC EXTENSION OF POLYFUNCTIONAL WORDS (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Polyfunctional words are words with special features in the Uzbek language. The phenomenon of polyfunctionality has been extensively studied in various languages. In particular, this phenomenon was explained in detail in the studies of M.V. Plyaskina, A.A.Leonenko, Ye.A.Starodumova, A.I.Zaitseva, S.G.Bolotova, N.N.Skripnikova, Ye.V.Sergeeva, A.V.Kravchenko, A.S.Krylova on the polyfunctionality of lexical units. O.S. Akhmanova explains the relationship between full-meaning and incomplete words as polyfunctionality, if "word similarity" is not violated, including: kak (how) (adjective and connective), kogda (when) (adverb and connective), ladno (harmonious, fair) (adverb and load), etc. This phenomenon is evaluated by other researchers in a similar way.